The mechanisms of nature-based therapy on depression, anxiety, stress, and life satisfaction: examining mindfulness in a two-wave mediation model - Kang, Minjung; Yang, Yeji; Kim, Hyunjin; Jung, Songhie; Jin, Hye-Young; Choi, Kee-Hong (Frontiers in Psychology, 2023)
Background Nature-based therapy (NBT), which centers around engaging in activities within natural surroundings, has consistently demonstrated therapeutic benefits for mental health. While NBT highlights the potential of nature as a therapeutic resource for promoting mental health, there is limited knowledge regarding its underlying mechanisms. Methods Two hundred seventy-six Korean participants (204 women, mean age = 54.99 ± 23.25 years) participated in a 30-session gardening program held twice weekly for 15 weeks. Structural equation modeling with a two-wave autoregressive cross-lagged model was used to investigate the mediating effects of mindfulness. Results NBT significantly improved the mean scores of all psychological variables. The mediation model was partially confirmed, with mindfulness at post-intervention (T2) mediating the relationship between baseline (T1) depression and anxiety and post-intervention (T2) life satisfaction. However, no significant indirect effect was observed between the path from stress (T1) to life satisfaction (T2). Conclusion Mindfulness is a crucial component for improving mental health outcomes. This study underscores the need to prioritize and emphasize mindfulness practices in NBT.